Line Clashing Probability Analysis of Catenary Anchored Leg Mooring with Quadraple Marine Hose Configuration - Gumilang Alhafiz; Murdjito; Eko Budi Djatmiko; Fajar Rachmadiarto (International Journal of Offshore and Coastal Engineering, 2026)
Global efforts to reduce carbon emissions have encouraged the adoption of lighter and more flexible offshore structures in support of Sustainable Development Goal (SDG) 13 and the International Maritime Organization (IMO) climate initiatives. This study investigates the technical performance of a Catenary Anchored Leg Mooring (CALM) terminal system connected to a Floating Storage and Offloading (FSO) facility using four subsea hose configurations of the Chinese lantern and lazy S types. Due to their flexibility, subsea hoses are susceptible to clashing under extreme environmental conditions, potentially causing damage and reducing operational reliability. Dynamic simulations were conducted to evaluate tensile forces, minimum bending radius, bending moments, shear forces, torsion moments, and the probability of hose clashing. Prior to the analysis, buoy stability was assessed following modifications to the hose configuration. The results indicate that the additional hose arrangement increased the buoy draft by 14.9% to 2.73 m. Under Accidental Limit State (ALS) conditions caused by anchor chain failure, structural loads on the hoses increased significantly, while the minimum bending radius decreased by 6%. Furthermore, the probability of hose clashing was substantially higher in ALS conditions than in Ultimate Limit State (ULS) conditions, demonstrating that anchor chain failure significantly increases the risk of subsea hose interaction and potential damage.